EFFECT OF LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE AT PT. HEVEA INDONESIA WORKS WITH WORK DISCIPLINE AS INTERVENING VARIABLE - Siahaan, Rumiris; Etri Jayanti, Suci; Margareth Sagala, Yomeini (RADJA PUBLIKA, 2022)
The results of this study indicate. (1) It can be seen that the magnitude of the adjusted R square value is 0.175 or 17.5%. This shows that Work Discipline (Z) and Leadership Style (X) can explain Employee Performance (Y) by 17.5%, the remaining 82.5% (100% - 17.5%) is explained by other variables outside the model. this research. (2) The results of the t-test (partial) can be seen that the obtained tcount (4,363) > ttable (2,048), as well as the significance value of 0.00 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the Leadership Style variable (X) positive and significant effect on Work Discipline (Z). (3) The results of the t-test (partial) can be seen that the value of tcount (1.917) ttable (2.048), and the significance value is 0.367 0, 05, it can be concluded that the second hypothesis is rejected, meaning that Leadership Style (X) has a significant effect on Employee Performance (Y). (4) The results of the path analysis test show that the direct effect of variable X on variable Y is 0.200. Meanwhile, the indirect effect through the Z variable is 0.636 x 0.329 = 0.2092. From the calculation results obtained, the indirect effect through the Z variable is greater than the direct effect on the Y variable.